Potential role of melastatin-related transient receptor potential cation channel subfamily M gene expression in the pathogenesis of urinary bladder cancer - Ceylan, Gulay Gulec; Onalan, Ebru Etem; Kuloglu, Tuncay; Aydog, Gulten; Keles, Ibrahim; Tonyali, Senol; Ceylan, Cavit (Spandidos Publ Ltd, 2016)
Urinary bladder cancer is one of the most common malignancies of the urinary tract. Ion channels and calcium homeostasis are involved in almost all basic cellular mechanisms. The transient receptor potential cation channel subfamily M (TRPM) takes its name from the melastatin protein, which is classified as potential tumor suppressor. To the best of our knowledge, there have been no previous studies in the literature investigating the role of these ion channels in bladder cancer. The present study aimed to determine whether bladder cancer is associated with mRNA expression levels of TRPM ion channel genes, and whether there is the potential to conduct further studies to establish novel treatment modalities. The present study included a total of 47 subjects, of whom 40 were bladder cancer patients and 7 were controls. Following the histopathological evaluation for bladder carcinoma, the mRNA and protein expression of TRPM were examined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry in tumor and normal tissues, in order to determine whether there is a difference in the expression of these channels in tumor and normal tissues. Immunoreactivity for TRPM2, TRPM4, TRPM7 and TRPM8 was observed in epithelial bladder cells in the two groups. RT-qPCR revealed a significant increase in TRPM7 expression in bladder cancer tissue compared to the controls (healthy bladder tissue), whereas no differences in TRPM2 or TRPM4 expression levels were observed. There were significant reductions in the expression levels of TRPM5 and TRPM8 in bladder cancer tissues. In the present study, the effects of TRP ion channels on the formation of bladder cancer was investigated. This study is instructive for TRPM2, TRPM4, TRPM5, TRPM7 and TRPM8 and their therapeutic role in bladder cancer. The results support the fact that these gens can be novel targets and can also be tested for during the treatment of bladder cancer.
Keywords: melastatin; transient receptor potential cation channel subfamily M; bladder cancer; gene; expression; immunohistochemistry; quantitative polymerase chain reaction